Linguocultural interpretation of the concept - Tokarev, G. V. (Cognition, Communication, Discourse, 2018)
This article discusses the principles of linguocultural interpretation of the concept. It outlines the main features of the concept as a macrostructure with respect to representations, naїve and scientific concepts, cultural attitudes, ideologies, stereotypes – constructive elements of the concept. The relations between these elements –  mental categories structuring the concept are analysed.